On Generalized Growth of Analytic Functions Solutions of Linear Homogeneous Partial Differential Equation of Second Order. (15th November 2017) - Kumar, Devendra
Abstract : The generalized growth parameters of analytic functions solutions of linear homogeneous partial differential equations of second order have been studied. Moreover, coefficients characterizations of generalized order and generalized type of the solutions represented in convergent series of Laguerre polynomials have been obtained.